Exploring causal relationships between inflammatory cytokines and allergic rhinitis, chronic rhinosinusitis, and nasal polyps: a Mendelian randomization study - Li, Li; Zhang, Yuanding; Liu, Hong; Wang, Tianqi; Li, Junxin; Wang, Xin (Frontiers in Immunology, 2023)
Objectives Previous research has suggested connections between specific inflammatory cytokines and nasal conditions, including Allergic Rhinitis (AR), Chronic Rhinosinusitis (CRS), and Nasal Polyps (NP). However, a lack of robust research establishing the causal underpinnings of them. This Mendelian Randomization (MR) study aims to evaluate the causal relationships between 41 inflammatory cytokines and the incidence of AR, CRS and NP. Methods This study employed a two-sample MR design, harnessing genetic variations derived from publicly accessible genome-wide association studies (GWAS) datasets. AR data was sourced from a GWAS with 25,486 cases and 87,097 controls (identifier: ukb-b-7178). CRS data originated from a GWAS encompassing 1,179 cases and 360,015 controls (identifier: ukb-d-J32). NP data was extracted from a GWAS involving 1,637 cases and 335,562 controls (identifier: ukb-a-541). The data for 41 inflammatory cytokines were obtained from an independent GWAS encompassing 8,293 participants. Inverse variance weighted (IVW), MR Egger regression and Weighted median were used to evaluate the causalities of exposures and outcomes. A range of sensitivity analyses were implemented to assess the robustness of the results. Results The results revealed significant associations between elevated circulating levels of MIP-1α (odds ratio, OR: 1.01798, 95% confidence interval, CI: 1.00217–1.03404, p = 0.02570) and TNF-α (OR: 1.01478, 95% CI: 1.00225–1.02746, p = 0.02067) with an augmented risk of AR in the IVW approach. Heightened levels of circulating IL-2 exhibited a positive correlation with an increased susceptibility to NP in the IVW approach (OR: 1.00129, 95% CI: 1.00017–1.00242, p = 0.02434), whereas elevated levels of circulating PDGF-BB demonstrated a decreased risk of NP (OR: 0.99920, 95% CI: 0.99841–0.99999, p = 0.047610). The MR analysis between levels of 41 inflammatory cytokines and the incidence of CRS yielded no positive outcomes. Conclusion This investigation proposes a potential causal association between elevated levels of MIP-1α and TNF-α with an elevated risk of AR, as well as an increased risk of NP linked to elevated IL-2 levels. Furthermore, there appears to be a potential association between increased levels of circulating PDGF-BB and a reduced risk of NP.